General e-learning framework - Leszek Rudak (Center for Open and Multimedia Eduacation of the University of Warsaw, 2012)
Most important components of the education are the student, the teacher and the content. In e-learning appears another, indispensable, component: the computer (understood as a whole computer systems and resources necessary to realization of distance education). The computer occupies the central place because is both a communication tool and a store of the content and materials. All relations, well-known from the traditional education (teacher - student, student - content and teacher - content) become derived relations, while the main ones are those between the computer and all other components of the teaching process.